Evaluating the impact of antiretroviral and antiseizure medication interactions on treatment effectiveness among outpatient clinic attendees with HIV in Zambia. (21st October 2020) - Navis, Allison; Dallah, Ifunanya; Mabeta, Charles; Musukuma, Kalo; Siddiqi, Omar K.; Bositis, Christopher M.; Koralnik, Igor J.; Gelbard, Harris A.; Theodore, William H.; Okulicz, Jason F.; Johnson, Brent A.; Sikazwe, Izukanji; et al.
Abstract: Objective: Interactions between enzyme‐inducing anti‐seizure medications (EI‐ASMs) and antiretroviral drugs (ARVs) can lead to decreased ARV levels and may increase the likelihood of viral resistance. We conducted a study to determine if co‐usage of ARVs and EI‐ASMs is associated with ARV‐resistant human immunodeficiency virus (HIV) among people living with HIV in Zambia. Methods: Eligible participants were ≥18 years of age and concurrently taking ASMs and ARVs for at least 1 month of the prior 6‐month period. Data were obtained regarding medication and HIV history. CD4 counts, plasma viral loads (pVLs), and HIV genotype and resistance profile in participants with a pVL >1000 copies/mL were obtained. Pearson's test of independence was used to determine whether treatment with EI‐ASM was associated with pVL >1000/mL copies. Results: Of 50 participants, 41 (82%) were taking carbamazepine (37 on monotherapy), and all had stable regimens in the prior 6 months. Among the 13 ARV regimens used, 68% had a tenofovir/lamivudine backbone. The majority (94%) were on a stable ARV regimen for >6 months. Median CD4 nadir was 205 cells/mm 3 (interquartile range [IQR] 88‐389), and 60% of participants had commenced ARV treatment before advanced disease occurred. Mean CD4 count at enrollment was 464 cells/mm 3 (SD 226.3). Seven participants (14%) had a CD4 count <200 cells/mm 3 . Four (8%) had a pVL >1000 copies/mL; all were on carbamazepine. Three participants with elevated pVL had a CD4 count <200 cells/mm 3 . None had documented adherence concerns by providers; however, two had events concerning for clinical failure. HIV genotype testing showed mutations in three participants. Carbamazepine was not found to correlate with elevated pVL ( P  = .58). Significance: EI‐ASMs are commonly used in sub‐Saharan Africa. Despite concurrent use of EI‐ASMs and ARVs, the majority of participants showed CD4 counts >200 cells/mm 3 and were virally suppressed. Carbamazepine was not associated with an increased risk of virological failure or ARV‐resistant HIV.